Early cinema in Scotland - Caughie, John (Edinburgh University Press Ltd, 2018)
Focusing on the social experience of cinema and cinema-going, this collection of essays provides a detailed context for the history of early cinema in Scotland, from its inception in 1896 until the arrival of sound in the early 1930s.
Keywords: Motion pictures -- Social aspects -- Scotland -- History -- 20th century.; Motion pictures -- Scotland -- History -- 20th century.; Cinéma -- Aspect social -- Écosse -- Histoire -- 20e siècle.; Cinéma -- Écosse -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- General.; Motion pictures -- Social aspects; Motion pictures; Scotland; 1900-1999; Electronic books.; History